Prevalence and characteristics of malaria among COVID-19 individuals: A systematic review, meta-analysis, and analysis of case reports. - Polrat Wilairatana; Frederick Ramirez Masangkay; Kwuntida Uthaisar Kotepui; Giovanni De Jesus Milanez; Manas Kotepui (Public Library of Science (PLoS), 2021)
Background The world population is currently at a very high risk of Coronavirus disease-2019 (COVID-19), caused by the severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2). People who live in malaria-endemic areas and get infected by SARS-CoV-2 may be at increased risk of severe COVID-19 or unfavorable disease outcomes if they ignore their malaria status. Therefore, the present study aimed to synthesize, qualitatively and quantitatively, information on the prevalence and characteristics of malaria infection among COVID-19-infected individuals. The findings will help us better understand this particular comorbidity during the COVID-19 pandemic. Methods The systematic review protocol was registered at the International Prospective Register of Systematic Reviews (PROSPERO) with the identification number: CRD42021247521. We searched for studies reporting on the coinfection of COVID-19 and malaria in PubMed, Web of Science, and Scopus from inception to March 27, 2021 using Medical Subject Headings (MeSH) terms. The study's methodological quality in the search output was assessed using the Joanna Briggs Institute (JBI) Critical Appraisal Tools for cross-sectional study. The pooled prevalence of Plasmodium spp. infection among patients infected with COVID-19 was estimated using the random effect model and then graphically presented as forest plots. The heterogeneity among the included studies was assessed using Cochrane Q and I2 statistics. The characteristics of patients co-infected with COVID-19 and malaria were derived from case reports and series and were formally analyzed using simple statistics. Results Twelve of 1,207 studies reporting the coinfection of COVID-19 and malaria were selected for further analysis. Results of quantitative synthesis show that the pooled prevalence of Plasmodium spp. infection (364 cases) among COVID-19 individuals (1,126 cases) is 11%, with a high degree of heterogeneity (95% CI: 4%-18%, I2: 97.07%, 5 studies). Most of the coinfections were reported in Nigeria (336 cases), India (27 cases), and the Democratic Republic of Congo (1 case). Results of qualitative synthesis indicate that patients with coinfection are typically symptomatic at presentation with mild or moderate parasitemia. An analysis of case reports and series indicates that co-infected individuals often display thrombocytopenia, lymphopenia, and elevated bilirubin levels. Among four patients (30%) who required treatment with intravenous artesunate, one experienced worsened clinical status after administering the drug. One serious outcome of coinfection involved a pregnant woman who experienced fetal abortion due to the initial misdiagnosis of malaria. Conclusions All individuals in malaria-endemic regions who are febrile or display symptoms of COVID-19 should be evaluated for malaria to avoid serious complications. Further prospective studies are required to investigate the burden and outcomes of COVID-19 in malaria-endemic regions. Prompt management is required to prevent serious outcomes in individuals co-infected with COVID-19 and malaria.